Quality standards and innovation in television production production processes in various fields - Kadhim Altai, Mustafa Hameed (ALBAHITH ALALAMI, 2018)
And the necessity for the progress of modern societies Because the scientific and objective characteristics that characterize modern societies and distinguish them from traditional societies, Is represented by the extent of its innovative achievements in the theoretical, applied and material scientific and spiritual fields. It should be noted that quality and innovation in modern societies is based on two main pillars, Standard measures for measuring and evaluating innovations to achieve their high quality, And the dissemination of the culture of innovation to spread awareness of the importance and conditions of success, and this is done by the advanced industrial countries, However, despite the great disparity between developed industrial countries and developing countries in areas of quality, creativity and innovation ,, This disparity is evident among developing countries among them as well , The United Arab Emirates was one of the countries that gave creativity and innovation extraordinary importance through the preparation of plans and conducting competitions and provide material and moral incentives , When it comes to television and the production of influential scenes in modern societies, The subject becomes even more important because of the importance of the media in changing the structures of societies, their people and their transformation into rich societies, In addition, television has become a recreational, educational and investment medium in most modern societies , Television drama has become a concern for individual communities, institutions, and nations, After the multiplicity of its functions and the number of followers. For these reasons, many media organizations have sought to develop their technical means and techniques and adopt innovation and creativity as a platform for excellence and quality. Innovation and creativity have become the focus of much of the modern world, which has adopted innovation and innovation as its approach to progress.